Simultaneous enhancement in the power factor and thermoelectric performance of copper sulfide by In2S3 doping. Issue 32 (29th July 2016) - Meng, Qing-Long; Kong, Shuang; Huang, Zhiwei; Zhu, Yuanhu; Liu, Heng-Chang; Lu, Xiaowei; Jiang, Peng; Bao, Xinhe
Abstract : Simultaneous enhancement in the power factor and thermoelectric performance of copper sulfide is realized by introducing In2 S3, which will be beneficial to the practical application. Abstract : In this work, we demonstrate simultaneous enhancement of the power factor and thermoelectric performance of Cu2 S upon the introduction of In2 S3 . The evident improvement in electrical conductivity, coupled with the less affected Seebeck coefficient, leads to a high power factor of 1361 μW m −1 K −2 at 850 K, which is much higher than the previously reported values for Cu2 S-based thermoelectric materials. Along with moderate thermal conductivity, a high ZT value of 1.23 at 850 K is achieved. Interestingly, the phase transitions and copper segregation of Cu2 S are also suppressed by In2 S3 doping due to the formation of the nanoscale CuInS2 phase. Such a high power factor, together with a decent ZT value and suppressed phase transitions and copper segregation, will be beneficial to its practical applications in thermoelectric power generation.